Solution
Generally ,the Laplace transform of a derivative is given by;
L{fn}=snF(s)-sn-1f(0)-sn-2f'(0)....fn-1(0)
Since the given boundary conditions don't give the x(0) and x'(0),
Take x(0)=A and x'(0)=B
The Laplace transform of the equation will be written as;
s2F(s)-sA-B+ F(s)=8cos2t-4sint
We know Laplace transform of cos at and sin at from the tables
Therefore;
(s2+1)F(s)-sA-B="\\frac{8s}{s^2+2^2}-\\frac{4}{s^2+1^2}"
Make F(s) the subject of the formula;
F(s)="\\frac{8s}{(s^2+4)(s^2+1)}" -"\\frac{4}{(s^2+1)(s^2+1)}"+"\\frac{sA}{s^2+1}" +"\\frac{B}{s^2+1}"
Using convolution method,it gives
x(t)=8cos2tsint-4sin2t+Acost+Bsint
x'(t)=8costcos2t-16sintsin2t-8costsint-Asint+Bcost
Apply the given conditions to find A and B
x(π/2)=-1
-1=8(-1)(1)-4(1)+A(0)+B(1)
B=11
x'(π/2)=0
0=8(0)(-1)-16(1)(0)-8(0)(1)-A(1)+B(0)
A=0
Therefore the particular solution is;
x(t)=8cos2tsint-4sin2t+11sint
Comments
Leave a comment